2012
DOI: 10.1016/j.clinbiochem.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of automated notification and customer service call centers for timely and accurate reporting of critical values: A laboratory medicine best practices systematic review and meta-analysis

Abstract: Objective-To conduct a systematic review of automatic notification methods and consider evidence-based recommendations for best practices in improving the timeliness and accuracy of critical value reporting.Results-196 bibliographic records were identified, with nine meeting review inclusion criteria. Four studies examined automated notification systems and five assessed call center performance. Average improvement from implementing automated notification systems is d = 0.42 (95% CI = 0.2 -0.62) while the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The study reported by Piva et al has taken forward their previous work [24,25], and the conclusions from the meta-analysis of Liebow et al [22], by auditing the actions taken by the physicians on receipt of the critical value alert. They showed that the three main actions were (a) initiation of new treatment in at least 90% of alerts, (b) further evaluation work -in at least 60% of alerts and (c) closer monitoring -in at least 25% of alerts.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The study reported by Piva et al has taken forward their previous work [24,25], and the conclusions from the meta-analysis of Liebow et al [22], by auditing the actions taken by the physicians on receipt of the critical value alert. They showed that the three main actions were (a) initiation of new treatment in at least 90% of alerts, (b) further evaluation work -in at least 60% of alerts and (c) closer monitoring -in at least 25% of alerts.…”
mentioning
confidence: 95%
“…Christenson et al described an initiative for collecting data from the use of tools developed and assessed in quality improvement programs [19,20]; the overall objective being "doing things right" [21], and to make better use of this type of observational data. These tools can take several forms, e.g., checklists, patient and specimen identifiers, and automatic alerts [22,23]. They are all designed to make practice more systematic … more precise.…”
mentioning
confidence: 99%
“…Examples of debatable issues include direct access to laboratory tests, and the direct reporting of laboratory results to the patient [37], aspects that, in the era of genomics, highlight the need for an approach based on ethics and patient safety, rather than on economics. For example, the notification of critical values has been described as a time-consuming and expensive activity that should be outsourced to call centers [38]. Yet critical results, which are frequently unexpected, may call for a change in treatment and can result in significant clinical benefit if issued promptly, and accompanied by clinical advice from laboratory professionals [39].…”
Section: Centralization or Decentralization Of Clinical Laboratoriesmentioning
confidence: 99%
“…improve health care quality. A number of LMBP systematic reviews have been published, including reports on patient specimen identification and the effectiveness of barcoding (5), critical value reporting (6), practices to reduce blood sample hemolysis in emergency departments (7), and cardiac biomarkers (8) and several in clinical microbiology (9,10).…”
mentioning
confidence: 99%